An increase in suppressive dendritic cells and T cells is a hallmark of healthy aging, a phenomenon exacerbated by cancer and modulated by chemo‐ and immunotherapy - Gardner, Joanne Karina (Curtin University, 2016)
This thesis showed that specialised immune cells, dendritic cells and T cells, that play a key role in protecting us from cancer become increasingly dysfunctional (suppressive) during aging, which is exacerbated by cancer. Moreover, anti-cancer chemotherapy and immunotherapy promote even more suppressive dendritic cells and T cells, which may explain reduced treatment efficacy in the elderly. The data suggest that combining chemotherapy and/or immunotherapy with strategies to alleviate immunosuppression may improve elderly cancer patient outcomes.